2017
DOI: 10.1038/s41467-017-01598-x
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility of the histone H3 tail in the nucleosome for binding of paired readers

Abstract: Combinatorial polyvalent contacts of histone-binding domains or readers commonly mediate localization and activities of chromatin-associated proteins. A pair of readers, the PHD fingers of the protein CHD4, has been shown to bivalently recognize histone H3 tails. Here we describe a mechanism by which these linked but independent readers bind to the intact nucleosome core particle (NCP). Comprehensive NMR, chemical reactivity, molecular dynamics, and fluorescence analyses point to the critical roles of intra-nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 53 publications
8
72
0
Order By: Relevance
“…In this study, we find that, in the absence of salt, accessibility of the nucleosomal H3 tail is increased by a factor of ~16 upon H2A/H2B dimer loss. These results align with investigations into the linked PHD fingers of CHD4, which bind the H3 tails in an 80bp-tetrasome with greater affinity than the 147bp-nucleosome 41 . This suggests that nucleosome composition will modulate accessibility of chromatin-associated proteins to the H3 tail.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In this study, we find that, in the absence of salt, accessibility of the nucleosomal H3 tail is increased by a factor of ~16 upon H2A/H2B dimer loss. These results align with investigations into the linked PHD fingers of CHD4, which bind the H3 tails in an 80bp-tetrasome with greater affinity than the 147bp-nucleosome 41 . This suggests that nucleosome composition will modulate accessibility of chromatin-associated proteins to the H3 tail.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies addressing histone tail accessibility in the context of the nucleosome have shown that the tails are significantly occluded within the nucleosome as compared to histone peptides or refolded histones 32,39,41,42 . In the case of the H3 tail, accessibility to chemical modification is reduced by a factor of ~250 at 50mM NaCl and ~10 at 150mM NaCl 41 . It has been proposed that accessibility to the H3 tail could be modulated by a number of factors including histone PTMs and DNA dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The slow passage of RNAPII through the 5' regions of genes increases the opportunity for HATs to access the histone tails resulting in increased acetylation in these regions. In support of this mechanism, the H3 tail becomes ten-fold less accessible when assembled into nucleosomes in vitro 53 and HAT activity is enhanced by disrupting interactions between DNA and the H3 tail 54 . Moreover, we show that nucleosome favoring sequences tend to accumulate both RNAPII and histone acetylation.…”
Section: Discussionmentioning
confidence: 94%